Polymyositis following Pandemic Influenza A (H1N1) and 2009-10 Seasonal Trivalent Vaccines. (15th August 2012) - Ferri, Clodoveo; Colaci, Michele; Manzini, Carlo Umberto; Sebastiani, Marco; Giuggioli, Dilia; Brugioni, Lucio
Abstract : Sporadic associations between inflammatory myopathies with vaccinations were described in the literature, raising the possible trigger value of vaccines in the development of these autoimmune disorders. Here, we reported the clinical history of 3 patients who developed polymyositis complicated by interstitial lung disease (2 cases) and dermatomyositis (1 case), after influenza A (H1N1) vaccination.